2023
DOI: 10.1186/s12885-023-10664-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 1-year tailored exercise program according to cancer trajectories in patients with breast cancer: study protocol for a randomized controlled trial

Abstract: Background Patients with breast cancer undergo various treatments according to their tumor subtype and cancer stages within 1 year after being diagnosed. Each treatment may cause treatment-related symptoms that have negative impacts on patients’ health and quality of life (QoL) The symptoms can be mitigated when exercise interventions are appropriately applied to patients’ physical and mental conditions. Although many exercise programs were developed and implemented during this period, the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Thus, according to the guidelines ( 7 , 39 , 40 ), patients were advised to engage in moderate physical activity, but no upper limit was mentioned. Even though, none of the BEGYN-1 study patients showed any sign of overexertion or other negative side effects of too much physical activity, further research is needed to individualize recommendations for the level of physical activity to aim for ( 50 , 51 ). The increased physical activity and fitness achieved in the BEGYN-1 study might have multiple other consequences that are known to be associated with increased physical activity in breast cancer patients, e.g., increased bone health ( 52 ), reduced cancer related fatigue ( 53 ), and reduced cancer related cognitive impairment ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to the guidelines ( 7 , 39 , 40 ), patients were advised to engage in moderate physical activity, but no upper limit was mentioned. Even though, none of the BEGYN-1 study patients showed any sign of overexertion or other negative side effects of too much physical activity, further research is needed to individualize recommendations for the level of physical activity to aim for ( 50 , 51 ). The increased physical activity and fitness achieved in the BEGYN-1 study might have multiple other consequences that are known to be associated with increased physical activity in breast cancer patients, e.g., increased bone health ( 52 ), reduced cancer related fatigue ( 53 ), and reduced cancer related cognitive impairment ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies looking at implementing remote or unsupervised exercise programs in a variety of cancer populations have been proposed and/or are ongoing. 85 , 94 , 95 , 96 , 97 …”
Section: Considerations and Opportunities For Implementing Exercise I...mentioning
confidence: 99%